CamBAfx: workflow design, implementation and application for neuroimaging - Ooi, Cinly; Bullmore, Edward T.; Wink, Alle-Meije; Sendur, Levent; Barnes, Anna; Achard, Sophie; Aspden, John; Abbott, Sanja; Yue, Shigang; Kitzbichler, Manfred; Meunier, David; Maxim, Voichita; et al. (Frontiers in Neuroinformatics, 2009)
CamBAfx is a workflow application designed for both researchers who use workflows to process data (consumers) and those who design them (designers). It provides a front-end (user interface) optimized for data processing designed in a way familiar to consumers. The back-end uses a pipeline model to represent workflows since this is a common and useful metaphor used by designers and is easy to manipulate compared to other representations like programming scripts. As an Eclipse Rich Client Platform application, CamBAfx's pipelines and functions can be bundled with the software or downloaded post-installation. The user interface contains all the workflow facilities expected by consumers. Using the Eclipse Extension Mechanism designers are encouraged to customize CamBAfx for their own pipelines. CamBAfx wraps a workflow facility around neuroinformatics software without modification. CamBAfx's design, licensing and Eclipse Branding Mechanism allow it to be used as the user interface for other software, facilitating exchange of innovative computational tools between originating labs.